Determination of Appropriate Livelihood Program and Development in a Rural Area - Mores, Jerson M.; Morgado, Christine T.; Mesana, James Patrick M. (Technium Social Sciences Journal, 2022)
This study aimed to determine the appropriate livelihood program and development in a rural area. A structured questionnaire was used in the study. This study presented the livelihood condition and livelihood needs through the identified assets that the community has. The study results showed that though they have natural assets, there are still limitations to utilizing them for their livelihood. They have a poor water supply, inferior to suitable housing, and poor sanitation. The community has labor capacity but limited skill due to lack of education and insufficient knowledge. The working population receives low wages and still earns below the poverty threshold. A strong family tie is present, as shown by the extended family relationship. Government assistance is obtained through senior citizen pensions and conditional cash transfer through the 4Ps program of the government. As a result, the community showed signs of poverty and needed support from the government. Some of the livelihood programs and improvements suggested were forming associations to access help and assistance, financial literacy, technical and vocational training, and mentoring programs. These suggestions could help in upgrading the livelihood condition of the community.